Pelatihan Senam Kebugaran Jasmani “Maumere Ceria” Pada Masyarakat Kampung Sadar, Desa Teluk Lada, Sobang-Pandeglang - Siti Sumarni; Idris Supriadi; Sukron Ma’mun; Devaron Suardi; Anna Laela; Rusmiyadi Rusmiyadi; Nurul Munajiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Maumere Gymnastic activities within the framework of the healthy living community movement (GERMAS) teluk lada village, sobang-pandeglang sub-district aiim to improve the health of skills in community gymnastic sports in teluk lada village, especially maumere gymanstic which is well known to the community and studied in schools. The purpose of this activity is to improve the skills of students who practice sport and the community in the field of cultural creation gymnastics, especailly maumere gymnastics, considering that this gymnastics has long been known by the community, from tradisional music to movement that are easy for childern to learn and can be enjoyed by young people. All levels of society, and is expected to improve public health in the area to support government activities, namely GERMAS.